Impaired immune surveillance accelerates accumulation of senescent cells and aging. Issue 1 (December 2018) - Ovadya, Yossi; Landsberger, Tomer; Leins, Hanna; Vadai, Ezra; Gal, Hilah; Biran, Anat; Yosef, Reut; Sagiv, Adi; Agrawal, Amit; Shapira, Alon; Windheim, Joseph; Tsoory, Michael; et al.
Abstract Cellular senescence is a stress response that imposes stable cell-cycle arrest in damaged cells, preventing their propagation in tissues. However, senescent cells accumulate in tissues in advanced age, where they might promote tissue degeneration and malignant transformation. The extent of immune-system involvement in regulating age-related accumulation of senescent cells, and its consequences, are unknown. Here we show thatPrf1 −/− mice with impaired cell cytotoxicity exhibit both higher senescent-cell tissue burden and chronic inflammation. They suffer from multiple age-related disorders and lower survival. Strikingly, pharmacological elimination of senescent-cells by ABT-737 partially alleviates accelerated aging phenotype in these mice. InLMNA +/G609G progeroid mice, impaired cell cytotoxicity further promotes senescent-cell accumulation and shortens lifespan. ABT-737 administration during the second half of life of these progeroid mice abrogates senescence signature and increases median survival. Our findings shed new light on mechanisms governing senescent-cell presence in aging, and could motivate new strategies for regenerative medicine. Senescent cells accumulate with aging contributing to age-related disease and the role of the immune system in removing senescent cells is not completely understood. Here, the authors show that perforin deficient mice accumulate more senescent cells and have a shorter lifespan, and that this phenotype can be reversed with administration of a senolytic drug.